1990
DOI: 10.1056/nejm199006143222402
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Treatment of Anemia Associated with Multiple Myeloma

Abstract: Anemia is a common complication of multiple myeloma. It resolves early in the disease if chemotherapy induces a complete remission, but persists if the disease progresses, causing disabling symptoms and often requiring blood transfusions. We treated 13 patients with myeloma-associated anemia by administering recombinant human erythropoietin three times a week for six months. Eleven patients (85 percent) had steady increases in hemoglobin levels and eventual correction of the anemia. Their symptoms of anemia su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
155
0
13

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(182 citation statements)
references
References 22 publications
14
155
0
13
Order By: Relevance
“…Again, any differences between groups may have been masked by the administration of blood transfusions or the effects of repeated chemotherapy. In common with previously published findings (Ludwig et al, 1990;Abels, 1993), treatment with both dosages of epoetin α showed excellent tolerability throughout the study. The incidence and type of adverse events did not differ markedly between the three groups, and epoetin α had no effect on the rate of premature study discontinuation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Again, any differences between groups may have been masked by the administration of blood transfusions or the effects of repeated chemotherapy. In common with previously published findings (Ludwig et al, 1990;Abels, 1993), treatment with both dosages of epoetin α showed excellent tolerability throughout the study. The incidence and type of adverse events did not differ markedly between the three groups, and epoetin α had no effect on the rate of premature study discontinuation.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies in anaemic chemotherapy-treated patients have shown increased haemoglobin (Hb) levels and decreased red blood cell (RBC) transfusion requirements following treatment with Epoetin alpha prevents anaemia and reduces transfusion requirements in patients undergoing primarily platinum-based chemotherapy for small cell lung cancer epoetin α in patients with a variety of malignant diseases; moreover, epoetin α was well-tolerated (Henry et al, 1989;Ludwig et al, 1990Ludwig et al, , 1993aLudwig et al, , 1993bAbels, 1993;Cascinu et al, 1993;Case et al, 1993). More recently a non-randomized phase IV study with data available on 2030 patients was reported.…”
mentioning
confidence: 99%
“…The costs and effects of EPO treatment in different patient groups have been widely discussed since the early 1990s [5,7]. In a study by Remák et al [8], the change in cost-effectiveness of epoetin alfa treatment versus RBCTs for patients with renal failure in the UK between the years 1990 and 2000 was analysed.…”
mentioning
confidence: 99%
“…It was the development of a human recombinant erythropoietin in 1983 [8] that allowed for the first innovative and effective treatment alternative for cancer-related anemia. A consistent body of evidence has since emerged, confirmed in numerous clinical trials, that treatment with erythropoietic agents in patients with anemia related to cancer and/or cancer treatment significantly decreases RBC transfusion requirements and increases hemoglobin (Hb) levels [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. More recently, improved quality of life (QOL) associated with the use of erythropoietic agents has also been confirmed in cancer patients [10-15, 23, 24].…”
Section: Introductionmentioning
confidence: 99%